2008
DOI: 10.1088/0022-3727/41/17/175205
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a pulsed-electron beam induced plasma: application to the growth of zinc oxide thin films

Abstract: Spatial and temporal distributions of species emitted from ablation of zinc oxide target by a pulsed-electron beam are studied by the complementary use of optical emission spectroscopy and camera fast imaging. We show that the slowest electrons produced by the accelerating tube in the pulsed-electron beam deposition (PED) system interact with the plasma plume and involve a further excitation of the neutrals species. The velocities of atoms and ions are found to be similar to those obtained in the well-known pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 31 publications
(44 reference statements)
4
17
0
Order By: Relevance
“…Experimental results have reported electron density values in the range of 10 22 -10 23 m -3 [15][16][17]. This is in accordance with our calculations, whereby the average electron density is ~10 23 m -3 .…”
Section: Model Assessmentsupporting
confidence: 91%
See 2 more Smart Citations
“…Experimental results have reported electron density values in the range of 10 22 -10 23 m -3 [15][16][17]. This is in accordance with our calculations, whereby the average electron density is ~10 23 m -3 .…”
Section: Model Assessmentsupporting
confidence: 91%
“…This is in accordance with our calculations, whereby the average electron density is ~10 23 m -3 . It has been found that the average temperature of the plasma varies from 1 eV to 1.25 eV [15,16]. The results based on our calculations indicate that the plasma temperature is ~1 eV, which is in quantitative agreement with the experimental data.…”
Section: Model Assessmentsupporting
confidence: 87%
See 1 more Smart Citation
“…1 is (0002) which is observed at 2h $ 34. 6 and is very close to that of the standard ZnO crystal (34.458). The absence of additional peaks in the XRD pattern excludes the possibility of any extra phases and/or large-size precipitates in the AZO films.…”
Section: Methodssupporting
confidence: 73%
“…Among all, it has been recently proposed that aluminum-doped zinc oxide ͑AZO͒ films can be the optimal choice as TCO layers in ZnO nanowire-based solar cells. [3][4][5] The optical, electrical, structural, and morphological properties of the TCO films are essential in determining device performances. Yet the remarkable combination of conductivity in an albeit wide-gap ͑i.e., transparent͒ material is not fully understood, along with the effect of dopants on charge transport: these issues contrast with the standard classification between zero-gap conductive and finite-gap optical materials and are still the subject of intense debate.…”
mentioning
confidence: 99%